Transformasi Al Quran Dan Hadis Dalam Novel BiografiMuhammad: Para Pengeja Hujan Karya Tasaro Gk: Tinjauan Intertekstualitas Dan Implementasinya Pada Mahasiswa Universitas Pekalongan - Tri Susilowati, Susilowati Tri; , Prof. Dr. Abdul Ngalim, M.M, M.Hum; , Dr. Nafron Hasyim (2015)
This research has five aims 1) to describe the relationship between episodes in the novel biography MPPH, 2) finding novel interfaces antarepisode in MPPH, 3) find a structure that builds novel MPPH biography as a work of transformation of the Qur'an and the Hadith as hipogram, 4) found intertextual relationship between biographical novel MPPH text with the text of the Qur'an and the Hadith as hipogram and 5) describe the implementation of Islamic teachings in the biographical novel MPPH in Pekalongan University students. This type of research is qualitative descriptive with the primary data source MPPH biographical novel GK Tasaro works as well as the Koran and the Hadith.MPPH biographical novel GK Tasaro works as well as the Koran and the Hadith. Data in the form of words, sentences, phrases that contain the values of Islam in the novel biography MPPH, the Koran and the Hadith. Data collection technique used is the technique see, record and technical literature. Data validation techniques using data triangulation and triangulation theory. Data analysis using a model of semiotic readings. The study of the relationship between the episode showed that each episode in the novel are interconnected and not autonomous. The relationship shown by the three interfaces between episodes, letters, gold silk scrolls and statements in the book (Zardusht). MPPH biographical novel structure shows that reflect the theme of human life which contains the issue of religion and tradition. Figure consists of imaginative characters and nonimajinatif. Character portrayed through dimensional figures physiological, psychological and sociological. Plot analysis using the concept of the Russian formalists , namely fabula and suzjet as well as presenting the motives that have been prepared artistically. Further background / setting consists of setting the time , place and background ambience background. Intertextual research found two results 1) text MPPH biographical novel is the transformation of the text of the Qur'an and Hadith. The relationship between the two, including expansion, 2) transformation of the teachings of Islam in the novel is done in two ways, first explicitly taken from verses of the Koran are quoted directly in the novel and both implicitly taken from the Koran and Hadith clamped on the pillars of faith and the pillars of Islam. The result of the research implemented to student Pekalongan University as a material of Prosa Fiction Studies at syllabus fourth semester.